DIAGNOSIS KELAYAKAN PENGEMBANGAN KLASTER INDUSTRI RUMPUT LAUT YANG BERKELANJUTAN - Yuli Wibowo; M Syamsul Ma'arif; Anas M Fauzi; Luky Adrianto (Agroindustrial Technology, University of Trunojoyo Madura, 2011)
This studyaimstodiagnose thefeasibility ofthe seaweedindustrycluster development using sustainable development approach.The aspectsanalyzedincludethe preconditions of ecological, economic, social, andinstitutional. The method used for analyzing includesheuristictechniques, independentpreference evaluation, and orderedweightedaveraging. Toaggregatethe preconditions of feasibility intoacompositevalue, the technique usedisan expert system. The analysis showed thatSumeneparea isfeasible todevelopthe seaweedindustry cluster